Transforming Theological Knowledge Essays on theology and the university after apartheid - Venter, Rian; Tolmie, Donald Francois (UJ Press, 2013)
A number of outstanding public intellectuals such as Jonathan Jansen, Crain Soudien and Lis Lange have been invited to present papers to clarify the conceptual challenge and what this might entail for theology. Well-known theologians such as Conrad Wethmar, Allan Boesak and Martin Prozesky reflect on the nature of theology and religion at universities amidst social exigencies. Two international theologians - Harold Attridge from the prestigious Yale Divinity School and Bram van de Beek from the Free University of Amsterdam - share their experiences of institutions that exemplify excellence and ecumenical openness.